Quadrotor stability using PID - Awang Besar, Julkifli (2013)
The quad rotor is an aerial vehicle whose motion is based on the speed of four motors. Due to its ease of maintenance, high maneuverability, vertical takeoff and landing capabilities (VTOL), etc., it is being increasingly used. The constraint with the quad rotor is the high degree of control required for maintaining the stability of the system. It is an inherently unstable system. There are six degrees of freedom – translational and rotational parameters. These are being controlled by 4 actuating signals. The x and y axis translational motion are coupled with the roll and pitch. Thus we need to constantly monitor the state of the system, and give appropriate control signals to the motors. The variation in speeds of the motors based on these signals will help stabilize the system. The unbalanced problem is one of the major problems for quad-rotor. The quad-rotor balance stability will disturb in case the disturbance exist such direct on it like a high wind speed or during outdoor flight. In this project will implement the PID controller for improving the quad-rotor selfbalancing system. The aim of this development